Avaliação da viabilidade técnica e econômica do uso de polietileno reciclado para produção de caixas d´água - Carvalho, Isadora Pradella (Universidade Federal de São Carlos, 2025)
The increasing generation of solid waste, driven by urbanization, economic expansion, and population growth, presents a significant environmental challenge. Plastics, whose global production has grown exponentially since 1950, are one of the main components of this waste, with only 20% being recycled. This study analyzed the technical and economic feasibility of using recycled polyethylene in the production of water tanks, promoting the circular economy. Mechanical tests demonstrated that recycled polyethylene exhibits adequate strength and stability, especially with optimized thicknesses, ensuring structural safety and functionality. Additionally, the water quality analysis revealed that the material does not compromise the pH of the stored fluid. Despite the increased weight compared to conventional water tanks, the use of recycled polyethylene proved to be a sustainable and technically viable alternative, although economically less attractive due to the high cost of the final product. The study concludes that advances in recycling processes could improve the competitiveness of this material, reducing its environmental impact and enhancing its potential for application.
Evaluation of the technical and economic feasibility of using recycled polyethylene for water tank production
Keywords: Resíduos; Reciclagem; Polietileno; Economia Circular; Testes Mecânicos; Waste; Recycling; Polyethylene; Circular Economy; Mechanical Tests; ENGENHARIAS::ENGENHARIA DE PRODUCAO::ENGENHARIA DO PRODUTO::DESENVOLVIMENTO DE PRODUTO